2005
DOI: 10.1038/sj.ijo.0802985
|View full text |Cite
|
Sign up to set email alerts
|

Impact of total and central obesity on vascular mortality in patients undergoing coronary angiography

Abstract: OBJECTIVE:To prospectively investigate the impact of total and central obesity on vascular mortality in patients undergoing coronary angiography. DESIGN: Prospective cohort study; mean follow-up 2.2 y. SUBJECTS: Men (n ¼ 513) and women (n ¼ 243) undergoing coronary angiography for the evaluation of coronary artery disease. MEASUREMENTS: Body mass index (BMI) was used as a measure of total obesity; waist-to-hip ratio (WHR) and waist circumference (WCf) as measures of central obesity. The primary study end point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 30 publications
0
28
0
3
Order By: Relevance
“…In particular, WHR is considered the traditional anthropometric technique for assessing CFM-to-PFM ratio (12). It is widely used and established in cross-sectional (35), longitudinal (36) and intervention studies, and it is a robust predictor of disease risk and mortality (35,37,38). In this context, WHR, rather than BMI, has therefore recently been recommended for the assessment of body fatness (38).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, WHR is considered the traditional anthropometric technique for assessing CFM-to-PFM ratio (12). It is widely used and established in cross-sectional (35), longitudinal (36) and intervention studies, and it is a robust predictor of disease risk and mortality (35,37,38). In this context, WHR, rather than BMI, has therefore recently been recommended for the assessment of body fatness (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, only central obesity is significantly and independently predictive of the 2-year vascular mortality in coronary patients. 20 Furthermore, it has been suggested that WC is a better measurement of central obesity than waist-hip ratio, 21 and it has been posited that WC is more closely correlated with an atherogenic lipid profile than waist-hip ratio. 22 Similarly, our study finds the mean values of TG and FBG and the mean values for abnormal metabolic parameters in the COG to be higher than in the GOG.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study in a consecutive series of 756 men or women undergoing coronary angiography evaluated the prognostic significance of abdominal obesity (waist circumference or waist-hip ratio) and BMI, with regard to clinical outcomes. 43 BMI did not correlate significantly with the incidence of vascular or all-cause mortality, or the incidence of major coronary events during an average of 2.2 years of prospective follow-up. In contrast, waist circumference correlated significantly with vascular mortality in men (OR adjusted for age smoking and cholesterol [2.3 (95% CI 1.2-4.6), P ¼ 0.017] and women [8.7 (95% CI 1.8-42.7), P ¼ 0.008], with similar results for waist-hip ratio.…”
Section: Abdominal Obesitymentioning
confidence: 99%